HOW TO CALCULATE OPERATIONS ON MATRICES USING EXCEL - Fazliddin Arzikulov; Valijon Makhsudov (Modern American Journals, 2025)
In the field of medicine: genetic data analysis, radiological image processing, statistical analysis, clinical research and biometric analysis, modeling of biological networks and systems, metabolic analysis and modeling, matrix insertion, matrix addition and subtraction, statistical analysis of matrix operations and mathematical methods, writing matrices in Excel and computing technologies are discussed.
Keywords: Genetic data, radiological imaging, statistical analysis, clinical research, biometric analysis, biological network, modeling, metabolic analysis, matrix, Excel program.